PERANCANGAN SISTEM INFORMASI PETTY CASH TERINTEGRASI BERBASIS VB.NET DAN MICROSOFT ACCESS - Ernawati; Haris Abu Bakar Sidik (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
In the early stages of operations, the Aprilia Cellular Counter did not have a structured petty cash management system, so transaction recording was still done manually without a clear recapitulation. This condition caused difficulties in monitoring cash flow, calculating balances, and preparing financial reports accurately and timely. This study aims to design and build a petty cash information system that is able to support the recording of petty cash transactions, balance management, and presentation of financial reports in a computerized manner. Data collection was carried out through observation, interviews, and literature studies. The system development used the Waterfall method which includes the stages of needs analysis, design, implementation, testing, and maintenance. The system was built with the VB.NET programming language, Microsoft Access as a database, and Crystal Report as a reporting medium. The results of the study indicate that the developed system can simplify the process of inputting cash inflows and outflows, accelerate the preparation of periodic reports, and present petty cash balance information in real time. Thus, this system is able to improve the orderliness of petty cash management and support more effective operational decision-making